The General Data Dissemination System (GDDS)-A Reflection on its First 12 Years and Plans for Taking it Forward - Kibuka, Robin (IMF Working Papers; Working Paper, 2009)
The paper reviews the developments in the last 12 years that have influenced the evolution of the IMF's General Data Dissemination System, leading to reforms to enhance its role. The GDDS itself is part of a broader IMF Data Standards Initiative launched in 1996 to help address macroeconomic data deficiencies, which contributed to the emerging economies' financial crisis during the early 1990s. The review takes stock of the experience with statistical technical assistance provided to member countries and the ongoing reforms, within and outside the IMF, to strengthen the GDDS. Such reforms are particularly relevant in the context of the ongoing economic and financial crisis, which once again underscores the role of statistics in guiding policymakers to strengthen defenses against future crises.